Endoscopic Urethral Recanalization In Men As A Standard Of Treatment (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article summarizes the results of the analysis of treatment data of 53 patients who underwent endoscopic recanalization of the obliterated urethra, followed by electroresection of scar tissue. Clinical studies have shown that relapses, after intervention, by the end of 1 year of observation, occur in 18.9% of patients.